2020
DOI: 10.48550/arxiv.2012.11799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enforcing exact physics in scientific machine learning: a data-driven exterior calculus on graphs

Abstract: As traditional machine learning tools are increasingly applied to science and engineering applications, physics-informed methods have emerged as effective tools for endowing inferences with properties essential for physical realizability. While promising, these methods generally enforce physics weakly via penalization. To enforce physics strongly, we turn to the exterior calculus framework underpinning combinatorial Hodge theory and physics-compatible discretization of partial differential equations (PDEs). Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…More recently, there has been efforts to add physical invariance to learned dynamics models, e.g., time-reversal symmetry [37]. Works pursuing related but distinct spatial-compatibility related to conservation structure other than geometric integration include: graph architectures with associated a data-driven graph exterior calculus [38], solving optimization problems with conservation constraint in latent space [39], and adding conservation constraints as a penalty in training loss [40]. The closest work to our approach is in [41], which proposed a time integrator that leverages the GENERIC (general equation for the nonequilibrium reversible-irreversible coupling) formalism to impose the structure, but enforces the degeneracy condition as penalty terms in the training loss objective.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, there has been efforts to add physical invariance to learned dynamics models, e.g., time-reversal symmetry [37]. Works pursuing related but distinct spatial-compatibility related to conservation structure other than geometric integration include: graph architectures with associated a data-driven graph exterior calculus [38], solving optimization problems with conservation constraint in latent space [39], and adding conservation constraints as a penalty in training loss [40]. The closest work to our approach is in [41], which proposed a time integrator that leverages the GENERIC (general equation for the nonequilibrium reversible-irreversible coupling) formalism to impose the structure, but enforces the degeneracy condition as penalty terms in the training loss objective.…”
Section: Related Workmentioning
confidence: 99%
“…image/language processing tasks, engineering and science models pose strict requirements on physical quantities to guarantee properties such as conservation, thermodynamic consistency and well-posedness of resulting models (Baker et al 2019). These structural constraints translate to desirable mathematical properties for simulation, such as improved numerical stability and accuracy, particularly for chaotic systems (Lee, Trask, and Stinis 2021;Trask, Huang, and Hu 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While so-called physics-informed ML (PIML) approaches seek to impose these properties by imposing soft physics constraints into the ML process, many applications require structure preservation to hold exactly; PIML requires empirical tuning of weighting parameters and physics properties hold only to within optimization error, which typically may be large (Wang, Teng, and Perdikaris 2020;Rohrhofer, Posch, and Geiger 2021). Structure-preserving machine learning has emerged as a means of designing architectures such that physics constraints hold exactly by construction (Lee, Trask, and Stinis 2021;Trask, Huang, and Hu 2020). By parameterizing relevant geometric or topological structures, researchers obtain more data-efficient hybrid physics/ML architectures with guaranteed mathematical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [33], and Zhou et al [34]. Note that related kernel-based NN methods, such as the work of Trask et al [35,36] exists and have been shown to be effective in physical applications. Also, Bronstein et al [28] provides an insightful perspective on applications of deep learning to non-Euclidean data, graphs, and manifolds as well as the relevant mathematics.…”
Section: Introductionmentioning
confidence: 99%